2020
DOI: 10.1016/j.geoderma.2019.113988
|View full text |Cite
|
Sign up to set email alerts
|

Wheat root system architecture and soil moisture distribution in an aggregated soil using neutron computed tomography

Abstract: Non-invasive techniques are essential to deepen our understanding of root-soil interactions in situ. Neutron computed tomography (NCT) is an example of such techniques that have been successfully used to study these interactions in high resolution. Many of the studies using NCT however, have invariably focused on lupine plants and thus there is limited information available on other more commercially important staple crop plants such as wheat and rice. Also considering the high neutron sensitivity to hydrogen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 68 publications
1
17
0
Order By: Relevance
“…The direct interaction between neutrons and hydrogen makes them ideally suited for imaging moisture transport. The study of this interaction has led to a variety of applications and includes soil and plant water distribution, which have been readily imaged. , Other work involved mapping the water uptake and vapor diffusion through wood adhesives . In conservation research studies, neutrons have been used to study water uptake in painting canvases and preparation layers and to visualize the spatial distribution of moisture in paintings .…”
Section: Introductionmentioning
confidence: 99%
“…The direct interaction between neutrons and hydrogen makes them ideally suited for imaging moisture transport. The study of this interaction has led to a variety of applications and includes soil and plant water distribution, which have been readily imaged. , Other work involved mapping the water uptake and vapor diffusion through wood adhesives . In conservation research studies, neutrons have been used to study water uptake in painting canvases and preparation layers and to visualize the spatial distribution of moisture in paintings .…”
Section: Introductionmentioning
confidence: 99%
“…The smallest detectable root diameter depends on the soil moisture (determining the transmission signal and the image contrast between root and soil) and the spatial resolution of the respective measurement. For plant containers with a diameter of 3 cm, the detection limit at moderate soil moisture usually ranges between 0.1 and 0.2 mm (e.g., Mawodza et al., 2020; Zarebanadkouki et al., 2019). Much finer roots (e.g., ≀0.05 mm) can be detected using high‐resolution detector setups.…”
Section: Limitations Of Neutron Imaging Techniquesmentioning
confidence: 99%
“…Along these lines, Wang et al (2017b) found that freeze-thaw cycles caused the enrichment of available Cd in > 2000 ÎŒm aggregate. Considering the high resistance of soil aggregates, most plant roots grow on the aggregate surfaces, especially the large macro-aggregates (Mawodza et al 2020). The increase and redistribution of available micronutrients caused by freeze-thaw cycles could contribute to the alleviation of available soil micronutrient deficiencies during the winterspring seasons, which would benefit plant growth and quality in the next growing season.…”
Section: Effects Of Ftcs On Bulk Soil and Aggregateassociated Available Micronutrientsmentioning
confidence: 99%
“…The volume of water expands during freezing when the liquid water becomes ice, thus increasing the disruption of aggregates, which is likely to increase desorption and release available micronutrients from soil minerals and soil organic matter (Li et al 2008). Therefore, in most cases, the influence of FTCs on bulk soil and aggregate-associated available micronutrients was enhanced by increased soil moisture content, especially in large macro-aggregates, which preferentially retained relatively higher soil moisture (Mawodza et al 2020). Notably, ongoing global warming is decreasing the thickness and duration of snow covers and accelerating the snow melts during winter and spring seasons, especially at temperate regions (IPCC 2007; Makoto et al 2014).…”
Section: Effects Of Smc On Bulk and Aggregate-associated Available Micronutrientsmentioning
confidence: 99%